Beyond RGD; nanoclusters of syndecan- and integrin-binding ligands synergistically enhance cell/material interactions. (December 2018) - Karimi, Fatemeh; Thombare, Varsha Jagannath; Hutton, Craig A.; O'Connor, Andrea J.; Qiao, Greg G.; Heath, Daniel E.
Abstract: Biomaterials are a powerful platform for directing cellular behaviour. Herein, we employed a biomimetic strategy to synthesize a low-fouling polymer functionalized with nano-scale clusters of ligands that bind both integrin and syndecan-4 receptors, as both receptor types are critical in focal adhesion signalling and mechanotransduction. Our results demonstrate that the presence of both ligand types synergistically increases the adhesion of human umbilical vein endothelial cells (more than a two fold increase after 4 h) and increases the rate of surface endothelialization compared to surfaces functionalized with only one ligand type. Additionally, we observe that the mixed population of ligands regulates endothelial cell migration, likely due to improved focal adhesion formation as observed through confocal microscopy. Furthermore, we illustrate that only endothelial cells cultured on these mixed ligand surfaces exhibit the appropriate morphological changes – elongation and alignment in the direction of flow - when exposed to laminar shear flow, and neither of the individual ligands alone is sufficient. These results illustrate that both receptor types must be engaged for optimum cell-material interactions and are mandatory for appropriate mechanotransduction. The results presented in this manuscript will be critical for the development of next generation biomedical devices and tissue engineering scaffolds. Graphical abstract: